The application of Rigidoporus sp J12 and Stenotrophomonas maltophilia BM in the degradation of batik waste - Subowo, Yohanes; Suliasih, Suliasih; Widawati, Sri (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
The batik industry in Indonesia produces batik waste which pollutes the environment. This waste can be degraded using laccase-producing microorganisms. The microorganisms used in the research were the fungus Rigidoporus sp J12 and the bacteria Stenotrophomonas maltophilia BM. This research aims to determine the ability of Rigidoporus sp J12 and Stenotrophomonas maltophilia BM and their consortium in producing laccase, observing their ability to degrade Poly R-478 which is an indicator of phenoloxidase activity and batik waste. Microorganisms are grown in growth media and then placed in media containing Poly R-478 or batik waste. Inducers are added to increase laccase activity. The inducers used were 15 g/L sucrose, 200 µM CuSO4 and 40 mM veratryl alcohol. The results showed that Rigidoporus sp J12 and Stenotrophomonas maltophilia BM produced laccase in PDB and NA media. The highest laccase activity was found in the enzyme produced by Rigidoporus sp J12 in PDB media at a temperature of 40°C, media pH 6.0 and the addition of sucrose. Rigidoporus sp J12 degraded batik waste by 39.38% and increased by 2.12 times after adding sucrose and incubation for 15 days. These bacteria and fungi can be used to degrade batik waste in order to prevent environmental pollution. Using the fungus Rigidoporus sp J12 purely is more profitable than using it with S. maltophilia BM bacteria.